10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BackgroundNeonatal hypoglycemia is a common, potentially serious postnatal metabolic disorder. This study evaluated the efficacy and safety of a single dose of 40% buccal dextrose gel versus standard care for achieving early euglycemia in at-risk neonates with a documented low baseline blood glucose.MethodsThis prospective randomized controlled trial was conducted at the Neonatal Intensive Care Unit, Minia University Hospital, Egypt (March-November 2024). Clinically stable, asymptomatic at-risk neonates (gestational age ≥34 weeks) with a documented low baseline blood glucose (below the maturity-specific operational threshold: <45 mg/dL for asymptomatic late-preterm/term infants and <30 mg/dL for preterm infants in the first 48 h) were randomized 1:1 to standard care alone or standard care plus a single 40% dextrose gel dose (0.5 mL/kg, buccal). The primary outcome was euglycemia (blood glucose ≥45 mg/dL) at 120 min, analyzed by intention-to-treat; infants requiring rescue intravenous dextrose before 120 minutes were counted as treatment failures.ResultsOf 120 screened neonates, 100 were randomized (50/group). By intention-to-treat, euglycemia at 120 minutes occurred in 82.0% (41/50) of the dextrose gel group versus 64.0% (32/50) of controls (absolute risk difference 18.0%, 95% CI 1.0-35.0; relative risk 1.28, 95% CI 1.00-1.64; number needed to treat = 6), a difference of borderline statistical significance (Pearson χ 2 p = 0.043; Fisher's exact p = 0.070). A secondary complete-case analysis (n = 90) showed a larger effect (91.1% vs 71.1%) but is potentially biased by exclusion of early treatment failures. Intravenous dextrose use during the study was numerically lower with gel (22.0% [11/50] vs 36.0% [18/50]; relative risk 0.61, 95% CI 0.32-1.16) but was not statistically significant. No intervention-related adverse events were observed during the 120-min study period.ConclusionsA single dose of 40% buccal dextrose gel improved early euglycemia in at-risk neonates by intention-to-treat analysis, with no intervention-related adverse events observed during the 120-min study period. These single-center findings are consistent with existing evidence and support further evaluation of buccal dextrose gel as a non-invasive first-line therapy, rather than establishing broad implementation.